Departamento de Patologia e Propedêutica Clínica - Castro, Alvimar Lima de; Okamoto, Ana Claudia; Soubhia, Ana Maria Pires; Carvalho, Antônio Augusto Ferreira de; Biasoli, Éder Ricardo; Ferreira, Elaine Cristina Francischini; Gaetti Jardim Junior, Elerson Gaetti Jardim Junior; Coclete, Gilberto Aparecido; Miyahara, Glauco Issamu; Vieira, João Batista; et al. (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Marcelo Macedo Crivelini